Differential associations between depressive symptoms and glycaemic control in outpatients with diabetes. Issue 3 (20th February 2013) - Bot, M.; Pouwer, F.; de, P.; Tack, C. J.; Geelhoed‐Duijvestijn, P. H. L. M.; Snoek, F. J.
Abstract Aims Depression is common in people with diabetes, and related to higher HbA1c levels. Depression, however, is a heterogeneous construct that involves a variety of symptoms. As little is known about the associations of individual depressive symptoms with HbA1c, we explored these associations in outpatients with diabetes. Methods The study was conducted in three tertiary diabetes clinics in the Netherlands. At baseline, the presence of the nine depressive symptoms that are listed in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition was assessed with the nine‐item Patient Health Questionnaire (PHQ‐9). At baseline and after a 1‐year follow‐up, HbA1c was derived from the medical charts. Results A total of 288 out of 646 subjects with diabetes (45%) reported one or more depressive symptom(s). Depressed mood (β = 0.11, P = 0.005), sleeping difficulties (β = 0.16, P < 0.001), appetite problems (β = 0.15, P < 0.001) and suicidal ideation (β = 0.14, P = 0.001) were significantly related to higher baseline HbA1c values. Furthermore, depressed mood (β = 0.09, P = 0.03) sleeping difficulties (β = 0.12, P = 0.004), appetite problems (β = 0.11, P = 0.01) and psychomotor agitation/retardation (β = 0.09, P = 0.04) were significantly related to higher HbA1c values at 1‐year follow‐up. Associations were more pronounced in Type 1 diabetes than in Type 2 diabetes. None of the depressive symptoms were related to change in HbA1c over time, except suicidal ideation. Conclusion In people with diabetes, several individual depressive symptoms were related to higher HbA1c levels. These associations persisted over time. More research is needed to investigate potential mechanistic pathways.